Improved Artificial Cooperative Search Algorithm for Solving Non-convex Economic Dispatch Problems with Valve-point Effects - Turgut, Oguz Emrah (Prof. Dr. Ismail SARITAS, 2018)
This paper presents Improved Artificial Cooperative Search (IACS) algorithm for solving economic dispatch problems considering the valve point effects, ramp rate limits, transmission losses and prohibited operation zones.Â Â In order to improve the solution quality and increase the search efficiency, a novel perturbation scheme called âGlobal best guided chaotic local searchâ is proposed and incorporated into ACS algorithm.Â Â The effectiveness of the proposed IACS algorithm has been benchmarked with twelve widely known optimization test problems.Â In order to assess the performance of the proposed algorithm on non-convex optimization problems,Â four case studies related to highly nonlinear economic dispatch problems have been solved . Results retrieved from IACS algorithm have been compared with literature approaches in terms of minimum, maximum and average generation cost values. Comparison results indicate that IACS produces more economical power load than those of other optimizers available in the literature